Evaluating the role of discourse markers and other enabling factors in academic listening comprehension - Gocheco, Paulina M. (Animo Repository, 2011)
The present study focuses on the analysis of a set of academic lecturers in the field of social science, one of the four sets of lectures developed in a previous study by Miciano, Gocheco, Bensal, and Abatayo (2009). The objective of the present study is to investigate the possible effects of discourse markers and other variables such as prior knowledge, test and lecture difficulty on lecture comprehension. The materials include two lecture versions for each topic - one with linguistic/discourse markers and one without. The listening test was taken by a total of 51 undergraduate and graduate students. The exploratory study shows no significant effect in the listening comprehension of academic lectures with or without discourse markers. Other factors that might explain the results, such as prior knowledge, lecture flow, test and lecture difficulty, were also examined in the present study.